Comparison between Subjective Sensations during First and Second Phacoemulsification Eye Surgeries in Patients with Bilateral Cataract - Ji-guo Yu; Ting Ye; Qing Huang; Yi-fan Feng; Jue Wang; Xun-an Fu; Yi Xiang (Journal of Ophthalmology)
Purpose. To evaluate and compare the subjective sensations reported by patients during first and second cataract extractions. Methods. Consecutive patients undergoing bilateral sequential cataract extraction using phacoemulsification were recruited. Following cataract surgery, patients completed questionnaires designed to evaluate subjective sensations, including anxiety, eye bulges, pain, and light sensitivity. Changes in painful sensations experienced by patients between the two surgeries were also recorded. Comparisons were also performed for each subjective sensation between different age groups (<50, 50–59, 60–69, 70–79, and >79 years). Results. A total of 127 patients were included in the final evaluation. Statistical comparison of the results showed that there were significant differences in perception of anxiety, eye bulges, and pain scores between the first and second cataract surgeries (P<0.05). However, there was no statistically significant difference for light sensitivity scores between the two surgeries (P=0.555). The differences in anxiety, perception of eye bulges, pain, and light sensitivity scores between both the surgeries showed no correlation with age (P>0.05 for all). Conclusions. Our research confirms the common observation that patients with bilateral cataracts often report more ocular discomfort during the second surgery. There are, therefore, additional factors that should be considered upon treating patients with bilateral cataracts, and the provision of preoperative counseling could play an important role in providing adequate patient care.